No guarantees, no trade: How banks affect export patterns - Friederike Niepmann; Tim Schmidt-Eisenlohr (Federal Reserve Bank of New York, 2013)
This study provides evidence that shocks to the supply of trade finance have a causal effect on U.S. exports. The identification strategy exploits variation in the importance of banks as providers of letters of credit across countries. The larger a U.S. bank's share of the trade finance market in a country is, the larger should be the effect on exports to that country if the bank reduces its supply of letters of credit. We find that supply shocks have quantitatively significant effects on export growth. A shock of one standard deviation to a country's supply of trade finance decreases exports, on average, by 2 percentage points. The effect is much larger for exports to small and risky destinations and in times when aggregate uncertainty is high. Our results imply that global banks affect export patterns and suggest that trade finance played a role in the Great Trade Collapse.
Keywords: F21; F23; F34; G21; 330; trade finance; global banks; letter of credit; exports; financial shocks